The Pengembangan E-Modul Peristiwa Trikora Untuk Meningkatkan Minat dan Pemahaman Sejarah Siswa Kelas XI SMK PGRI 2 Malang - Ramadhan, Rommy Naufal; Agung, Dewa Agung Gede; Widiadi, Aditya Nugroho (Cetta: Jurnal Ilmu Pendidikan, 2024)
Indonesian history is a subject that must be taught at the Vocational High School (SMK) level. Based on interviews with history teachers at SMK PGRI 2 Malang, it was found that students are less interested in learning history and there are still many students who get scores below the KKM (Minimum Completeness Criteria), which is 70. The objectives of the study were to produce e-modules of Trikora Events as history teaching materials for grade XI students of SMK PGRI 2 Malang, to test the effectiveness of e-modules of Trikora Events on the interest in learning history of grade XI students of SMK PGRI 2 Malang, and to test the effectiveness of e-modules of Trikora Events on the understanding of history of grade XI students of SMK PGRI 2 Malang. The place of research is SMK PGRI 2 Malang. This research used a research and development method which applied the ADDIE model. Data were collected through questionnaires and test questions. The data analysis technique uses validity analysis, student interest in history lessons after using e-modules and practicality and historical comprehension test of grade XI students. The results of the study came from material expert validators, teaching material expert validators, and students. The material expert validation score obtained a score of 95% with a very valid category, and was not revised, the score on the teaching material expert validation obtained a score of 82.14% which means very valid and not revised, the score on the small group trial to determine students’ interest in learning history scored 92.25% which means very valid and students are very interested in studying history, the practicality test obtained a score of 86, 33% which means very practical, the control class history comprehension test obtained an N-Gain score of 0.64, which means that the Trikora Event e-module is quite effective in increasing the understanding of the history of grade XI students of SMK PGRI 2 Malang, and the experimental class history comprehension test obtained a score of 0.66 which means it is quite effective in increasing the understanding of the history of grade XI students of SMK PGRI 2 Malang. So it is concluded that the developed e-module of Trikora Event is effective to increase the interest in learning history and historical understanding of grade XI students of SMK PGRI 2 Malang.